Implementing Micro, Small and Medium Enterprise Policy in Malaysia: Institutional Coordination, Strategic Empowerment, and Regulatory Oversight - Annisa Zahrah; Khelinban Sankar (Universitas Muhammadiyah Jakarta, 2025)
Micro, small and medium enterprises (MSMEs) occupy a strategic position in Malaysia’s development trajectory because they contribute substantially to national output, employment creation, entrepreneurial inclusion, and regional economic resilience. Nevertheless, the contribution of MSMEs does not emerge automatically; it depends on the quality of policy implementation, the effectiveness of institutional coordination, the capacity of target groups, and the adaptability of public programmes to changing economic conditions. This article examines the implementation of MSME development policy in Malaysia by focusing on the regulatory architecture, inter-agency coordination, empowerment strategies, access to finance, digital transformation, and partnership oversight. The study uses a qualitative documentary research design based on policy documents, official statistical reports, academic literature, and relevant secondary sources. The analysis is informed by public policy implementation theory, particularly the interaction between idealised policy, target groups, implementing organisations, and environmental factors. The findings show that Malaysia has developed a relatively comprehensive MSME policy ecosystem through institutions such as the National Entrepreneur and SME Development Council, SME Corporation Malaysia, SME Bank, and other ministries and agencies. Policy implementation is supported by long-term national plans, entrepreneurship strategies, capacity-building programmes, financing schemes, digitalisation initiatives, and competition-law enforcement. However, implementation challenges remain, especially in bureaucratic fragmentation, uneven access to financing, digital capability gaps, limited managerial capacity among micro-enterprises, and the difficulty of integrating informal or low-productivity enterprises into higher-value markets. The article argues that Malaysia’s MSME policy implementation is best understood as an evolving governance system rather than a single programme.